Characterization of DNA Methylation Associated Gene Regulatory Networks During Stomach Cancer Progression - Wu, Jun; Gu, Yunzhao; Xiao, Yawen; Xia, Chao; Li, Hua; Kang, Yani; Sun, Jielin; Shao, Zhifeng; Lin, Zongli; Zhao, Xiaodong (Frontiers in Genetics, 2019)
DNA methylation plays a critical role in tumorigenesis through regulating oncogene activation and tumor suppressor gene silencing. Although extensively analyzed, the implication of DNA methylation in gene regulatory network is less characterized. To address this issue, in this study we performed an integrative analysis on the alteration of DNA methylation patterns and the dynamics of gene regulatory network topology across distinct stages of stomach cancer. We found the global DNA methylation patterns in different stages are generally conserved, whereas some significantly differentially methylated genes were exclusively observed in the early stage of stomach cancer. Integrative analysis of DNA methylation and network topology alteration yielded several genes which have been reported to be involved in the progression of stomach cancer, such as IGF2, ERBB2, GSTP1, MYH11, TMEM59, and SST. Finally, we demonstrated that inhibition of SST promotes cell proliferation, suggesting that DNA methylation-associated SST suppression possibly contributes to the gastric cancer progression. Taken together, our study suggests the DNA methylation-associated regulatory network analysis could be used for identifying cancer-related genes. This strategy can facilitate the understanding of gene regulatory network in cancer biology and provide a new insight into the study of DNA methylation at system level.